2021
DOI: 10.3390/diagnostics11091588
|View full text |Cite
|
Sign up to set email alerts
|

Flap Thickness and the Risk of Complications in Mechanical Microkeratome and Femtosecond Laser In Situ Keratomileusis: A Literature Review and Statistical Analysis

Abstract: Introduction: A recent Cochrane review found no difference in visual acuity outcomes between femtosecond-assisted laser in situ keratomileusis (LASIK) and LASIK using mechanical microkeratomes (MMKs). This study compares the flap thickness and risk of complications related to flap creation using femtosecond lasers and MMKs. Methods: PubMed and the Web of Science are used to search the medical literature. An extensive search is performed to identify the flap thickness and complications of LASIK as reported up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…Contrary to that Kanclerz P et al have shown that the evidence of the superiority of one technique in terms of complications over another cannot be stated. 20 In our study the resultant corneal flap thickness was found as 101.18 ± 3.51 in right eye (p < 0.05) and 100.61 ± 3.49 in left eye (p > 0.05) which was statistically significant in right but insignificant in left eye respectively from the predicted value. There is a highly significant mean difference in resultant corneal flap thickness (P < 0.0001) of right and left eye.…”
Section: Discussionmentioning
confidence: 40%
“…Contrary to that Kanclerz P et al have shown that the evidence of the superiority of one technique in terms of complications over another cannot be stated. 20 In our study the resultant corneal flap thickness was found as 101.18 ± 3.51 in right eye (p < 0.05) and 100.61 ± 3.49 in left eye (p > 0.05) which was statistically significant in right but insignificant in left eye respectively from the predicted value. There is a highly significant mean difference in resultant corneal flap thickness (P < 0.0001) of right and left eye.…”
Section: Discussionmentioning
confidence: 40%
“…It is more difficult to achieve an even thickness flap using mechanical keratome vs femtosecond laser. 3 Increased thickness of the flap leads to greater rotational forces, which tends to produce folds at the nasal hinge, as seen in this patient. 4 In addition, uneven thickness can cause microdisplacements.…”
Section: Majid Moshirfar MD Facs Jenna Jensen Bs Carter Payne Bsmentioning
confidence: 69%
“…Flap looked like a meniscus flap suggestive of microkeratome LASIK. 6 CFB caused a buttonhole in the flap with the flap margin delineated inferiorly ( Fig. 2 b).…”
Section: Case Descriptionmentioning
confidence: 99%
“… 2 Post-LASIK patients have a risk of suffering additional flap related complications when sustaining trauma or foreign body (FB) fall. 3 Occurrence and management of trauma related flap complications like flap tear, avulsion, diffuse lamellar keratitis (DLK), 4 , 5 , 6 etc have been well reported in literature but there are very few reports describing the incidence of penetrating trauma or corneal foreign bodies (CFB) and their management. Post-LASIK eyes in addition to routine foreign body work up require careful inspection of flap and stromal bed.…”
Section: Introductionmentioning
confidence: 99%